Struktur Komunitas Uca Sp Di Kawasan Teluk Benoa Pada Karakteristik Substrat Yang Berbeda - Loviasari, Ni Wayan; As-syakur, Abd. Rahman; Faiqoh, Elok; Dirgayusa, I Gusti Ngurah Putra; Wiyanto, Dwi Budi (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018), 2017)
The mangrove ecosystem is home to a variety of fauna, ranging from water animals to primates, as a breeding ground for a variety of aquatic animals such as fish, crustaceans, crabs and mollusks, as well as a place to feed a number of wildlife such as reptiles and mammals. Uca sp is one of the fauna that utilizes and helps mangrove in its ecological balance. This research was conducted on 3 mangrove areas with the purpose of knowing the types and structure of Uca sp community on different substrate characteristics, where in Mertasari mangrove have the type of sandy substrate, Muara Waduk Nusa Dua Denpasar has kind of sandy loam substrate and Tanjung Benoa has kind sandy substrate. The sampling time was conducted in December 2016 when the lowest tide of the month. Determination of stations taken at each research location (station) using purposive sampling method. From the results of the study found Uca sp as many as 5 types, namely Uca cryptica, Uca dussumieri, Uca rosea, Uca cryptica and Uca crassipes. The highest density of Uca sp that is at station 2 located in Muara Waduk Nusa Dua Denpasar is 52,75 ind/m 2 and lowest at station 3 in Tanjung Benoa get 32,25 ind /m 2 . The index values ??of the diversity of the three research stations are categorized into low diversity. In all three research stations categorized into uniformity index with depressed community or low uniformity. Based on the calculation on the three stations have a high dominance index.